2018
DOI: 10.1159/000488078
|View full text |Cite
|
Sign up to set email alerts
|

Serial Assessment of Growth Factors Associated with Liver Regeneration in Patients Operated with Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy

Abstract: Background: There is limited knowledge about the mechanisms behind the unparalleled growth of the future liver remnant (FLR) linked to associating liver partition and portal vein ligation for staged hepatectomy (ALPPS). In this study, liver regenerative markers were examined in patients subjected to ALPPS. Methods: Ten patients with colorectal liver metastases treated with neoadjuvant chemotherapy and ALPPS were included. Plasma was sampled at 6 time points and biopsies from both liver lobes were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Thirteen single cohort observational studies, described serum IL-6 concentration in association with liver regeneration or PHLF 31 43 . Seven studies described peak concentration on first postoperative day after hepatectomy, with mean values ranging from 55.5 to 1027 pg/ml 34 , 38 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen single cohort observational studies, described serum IL-6 concentration in association with liver regeneration or PHLF 31 43 . Seven studies described peak concentration on first postoperative day after hepatectomy, with mean values ranging from 55.5 to 1027 pg/ml 34 , 38 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen single cohort observational studies, described serum IL-6 concentration in association with liver regeneration or PHLF 31 43 . Seven studies described peak concentration on first postoperative day after hepatectomy, with mean values ranging from 55.5 to 1027 pg/ml 34 , 38 43 . One study described the IL-6 peak concentration between day of operation and first postoperative day 37 and two studies reported the peak on the day of the operation during the early post-hepatectomy phase 32 , 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALPPS procedures resulted in a peak of IL-6 levels after stage 1, which decreased rapidly and did not increase after stage 2. Furthermore, a correlation between the peak IL-6 levels and HGF was detected [46]. In the setting of human living donor liver transplantation, higher levels of serum IL-6 were independently associated with increased graft volumes during the first postoperative week [147].…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 88%
“…After a recovery period of 1-2 weeks, Stage 2 is performed in which the deportalized liver is removed to render the patient completely tumor-free [45]. Furthermore, HGF levels were found to be significantly elevated on PODs 1, 7, and 14 after living donor hepatectomy and were correlated with recipient liver volumes on POD 14 [11,[46][47][48][49][50][51][52][53][54][55]. Tomiya et al reported an association of serum HGF levels with hepatocellular dysfunction and systemic inflammation [56].…”
Section: Growth Factorsmentioning
confidence: 99%